Characterizing adaptations of prosthetic feet in the frontal plane. (August 2020) - Ernst, Michael; Altenburg, Björn; Schmalz, Thomas
Background: Energy-storage and return feet incorporate various design features including split toes. As a potential improvement, an energy-storage and return foot with a dedicated ankle joint was recently introduced allowing for easily accessible inversion/eversion movement. However, the adaptability of energy-storage and return feet to uneven ground and the effects on biomechanical and clinical parameters have not been investigated in detail. Objectives: To investigate the design-related ability of prosthetic feet to adapt to cross slopes and derive a theoretical model. Study design: Mechanical testing and characterization. Methods: Mechanical adaptation to cross slopes was investigated for six prosthetic feet measured by a motion capture system. A theoretical model linking the measured data with adaptations is proposed. Results: The type and degree of adaptation depends on the foot design, for example, stiffness, split toe or continuous carbon forefoot, and additional ankle joint. The model used shows high correlations with the measured data for all feet. Conclusions: The ability of prosthetic feet to adapt to uneven ground is design-dependent. The split-toe feet adapted better to cross slopes than those with continuous carbon forefeet. Joints enhance this further by allowing for additional inversion and eversion. The influence on biomechanical and clinical parameters should be assessed in future studies. Clinical relevance: Knowing foot-specific ability to adapt to uneven ground may help in selecting an appropriate prosthetic foot for persons with a lower limb amputation. Faster and more comprehensive adaptations to uneven ground may lower the need for compensations and therefore increase user safety.